Quantifying the apparent 'Catalytic' effect of porous electrode surfaces - Ward, K; Compton, R (Elsevier, 2014)
The voltammetry of porous electroactive surfaces is investigated by simulation. The surface is modelled as a solid block penetrated by a regularly distributed array of cylindrical pores. The effect of the voltage scan rate and the geometry (in terms of pore depth, radius, and inter-pore separation) of the porous surface on the voltammetry is examined for both fully reversible and fully irreversible electrode kinetics. In the latter case, it is demonstrated that when the pores are relatively shallow, a predictable shift in peak potential is observed corresponding to an apparent catalytic effect. For deeper pores, voltammetry corresponding to thin-layer behaviour is observed. The limits under which these behaviours operate are elucidated. This work builds on a previous investigation into the apparent catalytic effect exhibited by nanoparticle modified electrodes Ward et al. (2013) [11]. © 2014 Elsevier B.V. All rights reserved.